2022
DOI: 10.1007/s12070-021-03015-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Scoring Assessment as a Prognostic Tool in Covid-19 Associated Mucormycosis: A Short-Term Observational Study

Abstract: To introduce an intraoperative scoring system for covid-19 associatedmucormycosis An observational study conducted among 43 cases of confirmed CAM whichincluded 35 males and 8 females, with an average age of 56 years. The surgicalapproach adopted in our cases included endoscopic surgical debridement withDenker's approach including mandatory pterygopalatine and infratemporal fossaexploration. All cases were intraoperatively scored using our designed intraoperativescoring assessment tool for mucormycosis. Postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, studies including patients with invasive fungal infections in general, and not mucormycosis specifically, and studies including mucormycosis cases not associated with COVID-19 and not separately with CAM cases were excluded. Sixteen studies were excluded due to unavailable–insufficient information [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Four studies were excluded as they included patients with non-microbiologically confirmed SARS-CoV-2 infection [ 25 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies including patients with invasive fungal infections in general, and not mucormycosis specifically, and studies including mucormycosis cases not associated with COVID-19 and not separately with CAM cases were excluded. Sixteen studies were excluded due to unavailable–insufficient information [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Four studies were excluded as they included patients with non-microbiologically confirmed SARS-CoV-2 infection [ 25 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%